2022
DOI: 10.1051/0004-6361/202142614
|View full text |Cite
|
Sign up to set email alerts
|

The Westerbork Coma Survey

Abstract: We present the blind Westerbork Coma Survey probing the H I content of the Coma galaxy cluster with the Westerbork Synthesis Radio Telescope. The survey covers the inner ∼1 Mpc around the cluster centre, extending out to 1.5 Mpc towards the south-western NGC 4839 group. The survey probes the atomic gas in the entire Coma volume down to a sensitivity of ∼1019 cm−2 and 108 M⊙. Combining automated source finding with source extraction at optical redshifts and visual verification, we obtained 40 H I detections of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 130 publications
4
12
0
Order By: Relevance
“…Most U types are distributed in the first and second quadrants, with only a few in the fourth quadrant. The absence of galaxies in the fourth quadrant is similar to the RPS galaxies explored by Molnar et al (2022). We also find that more strongly warped U types prefer the first quadrant.…”
Section: Stellar Mass Star Formation Rate and Gas Mass Fractionsupporting
confidence: 77%
See 1 more Smart Citation
“…Most U types are distributed in the first and second quadrants, with only a few in the fourth quadrant. The absence of galaxies in the fourth quadrant is similar to the RPS galaxies explored by Molnar et al (2022). We also find that more strongly warped U types prefer the first quadrant.…”
Section: Stellar Mass Star Formation Rate and Gas Mass Fractionsupporting
confidence: 77%
“…Similarly, Mun et al (2021) showed that the HI deficiency of RPS galaxies in the Virgo cluster strongly depends on the evolutionary phase of infall. Molnar et al (2022) investigated RPS galaxies in the Coma cluster and showed using a simple model that the distribution of Δf HI and ΔsSFR can trace the evolutionary phase of RPS. The residual of f HI , Δf HI , is defined by the difference in f HI between the warp sample and the mean f HI of its corresponding control sample.…”
Section: Stellar Mass Star Formation Rate and Gas Mass Fractionmentioning
confidence: 99%
“…6). As a matter of fact, the central regions of A85 could be an extreme case even compared with Coma, where a number of gas deficient spirals are still detected within 1 Mpc, with similar Hi mass limit detection than the present work (Bravo-Alfaro et al 2000;Healy et al 2021;Molnár et al 2022). In A85 the only Hi projected close to the center is the high-speed infalling jellyfish JO201, which shows signs of strong ram pressure stripping (Ramatsoku et al 2020;Luber et al 2022).…”
Section: Global Properties Of the Studied Clusterssupporting
confidence: 66%
“…Several studies have been devoted to the nearest clusters such as Virgo, Hydra, A 1367 and Coma (e.g. Giovanelli & Haynes 1985;Cayatte et al 1990;Bravo-Alfaro et al 2000;Solanes et al 2001;Chung et al 2009;Scott et al 2010Scott et al , 2018Boselli et al 2021;Wang et al 2021;Molnár et al 2022). The large coverage and high sensitive Hi-surveys carried out with single dish telescopes, such as HIPASS and ALFALFA (Giovanelli et al 2005;Haynes et al 2018), provided statistical information on the Hi content of large samples of spirals in different environments.…”
Section: Introductionmentioning
confidence: 99%
“…To better understand the formation and evolution of galaxies in various global and local environments, a next step is to analyse the morphological properties of galaxies in more detail than in the present study. For this purpose, one could use data on galaxies in our local cosmic neighbourhood, such as those provided by Quilley & de Lapparent (2022), and future multi-wavelength surveys with detailed information on galaxies, such as the J-PAS survey, or the HI Westerbork Coma Survey (Molnár et al 2022), which showed that cluster galaxies are HI deficient in comparison with galaxies found around the cluster. Were galaxies born similar, turning into ellipticals or spirals during evolution in hugely different environments, or are the seeds of primeval galaxies already different?…”
Section: Discussionmentioning
confidence: 99%